Hertzsprunging into the Unknown : Understanding Current Detection Limits for Exoplanets Around Hot Stars - Meredith, Zachary; Miller, Nathan A. (My University, 2018)
The field of exoplanet research has rapidly grown over the past two decades, with more being discovered every day. There was a particular period of growth in the number of known exoplanets around the year 2009 with over four thousand likely new systems discovered through the Kepler mission. This research narrows the search to characteristics of planetary systems around hot (OBtype) stars. Unfortunately, we were unable to find evidence of any planets orbiting OB stars in NASA’s exoplanet database using a search by object type. By cross-referencing the NASA Exoplanet Archive and with the SIMBAD general database of astronomical objects, we confirmed that there were indeed OB stars in the field of view monitored by the Kepler spacecraft. This indicates there is a true deficit in the number of detected exoplanets around OB-type stars. To explain this deficit, we explored the sensitivity limits for the radial velocity and transit methods currently responsible for most exoplanet detections. We determined that due to the size and mass of OB-type stars, any planets orbiting them would be below the current levels of detectability.
Color poster with text, images, charts,and graphs.
Keywords: O stars; B stars; Radial velocity; Extrasolar planets; Posters